Bismuth Fundamentals and Optoelectronic Applications - Luo, Yanhua; Wen, Jianxiang; Zhang, Jianzhong (IntechOpen, 2020)
Bismuth-a wonder metal with unique features-plays an important role in the bismuth-related optoelectronic materials. The innovative development of bismuth optoelectronic materials will undoubtedly drive the social development and economic growth in the world towards a glorious future.